The New Real : Media and Mimesis in Japan from Stereographs to Emoji - Abel, Jonathan E., 1971- (Book collections on Project MUSE., 2023)
"A synthetic history of new media reception in modern and contemporary Japan, The New Real positions mimesis at the heart of the media concept. Considering both mimicry and representation as the core functions of mediation and remediation, it offers a new model for media studies while explaining the deep and ongoing imbrication of Japan in the history of new media"--